Competing Premarital Investments - Peters, Michael; Siow, Aloysius (Journal of Political Economy, 2002)
This paper studies premarital parental investments in children’s wealth, where spousal wealth is a public good in marriage. By investing in their children’s wealth, parents increase the wealth of their children and the quality of the spouses that their children can marry. In large marriage markets, the hedonic return to investment internalizes all the external benefits of premarital investment in wealth so that the competitive equilibrium is efficient. Marriage market competition also increases investments in small marriage markets relative to no competition, but equilibrium investments are not efficient.